2019
DOI: 10.1007/s00221-018-05466-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cognitive load on processing efficiency and performance effectiveness in anxiety: evidence from event-related potentials and pupillary responses

Abstract: Anxiety has been associated with poor attentional control, as reflected in lowered performance on experimental measures of executive attention and inhibitory control. Recent conceptualisations of anxiety propose that individuals who report elevated anxiety symptoms worry about performance and will exert greater cognitive effort to complete tasks well, particularly when cognitive demands are high. Across two experiments we examined the effect of anxiety on task performance and across two load conditions using (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…Higher No-go-N2 amplitudes were found for anxious in comparison to non-anxious individuals (Righi et al, 2009;Sehlmeyer et al, 2010), indicating enhanced cognitive control required to inhibit prepotent responses (Righi et al, 2009). In contrast, Yang and Li (2014) and Hepsomali et al (2019) found no difference in No-go-N2 depending on trait anxiety. We expected larger ERP amplitudes for participants with higher trait social anxiety of the P1 and No-go-N2, depending on emotion category.…”
Section: Supplement A: Individual Differencesmentioning
confidence: 80%
See 1 more Smart Citation
“…Higher No-go-N2 amplitudes were found for anxious in comparison to non-anxious individuals (Righi et al, 2009;Sehlmeyer et al, 2010), indicating enhanced cognitive control required to inhibit prepotent responses (Righi et al, 2009). In contrast, Yang and Li (2014) and Hepsomali et al (2019) found no difference in No-go-N2 depending on trait anxiety. We expected larger ERP amplitudes for participants with higher trait social anxiety of the P1 and No-go-N2, depending on emotion category.…”
Section: Supplement A: Individual Differencesmentioning
confidence: 80%
“…In correct response trials, the mean EPN amplitude was extracted between 250 and 300ms after stimulus onset in an occipito-parietal electrode cluster including electrodes O1, O2, P9, P10, PO7 and PO8 (Kulke, 2019); the mean LPC amplitude in a time window between 400 and 600ms after stimulus onset in an occipito-parietal electrode cluster including Pz, POz, PO3 and PO4 (Kulke, 2019); the mean N170 amplitudes were quantified in a time window between 130-200 ms after stimulus onset in a posterior electrode cluster (P7, P8, PO7, PO8, PO3, PO4, PO5, PO6) (Hinojosa et al, 2015). The mean No-go-N2 was determined only for correct No-go trails between 200-350ms in a frontocentral electrode cluster (Fz, F3, F4, Cz, C3, C4, FCz), based on previous research (Hepsomali, Hadwin, Liversedge, Degno, & Garner, 2019;Righi, Mecacci, & Viggiano, 2009;Sehlmeyer et al, 2010). The frontal response was quantified between 100 and 180 ms in a frontal cluster (F3, FC5, FC3, FC1, C3, F4, FC2, FC4, FC6, C4).…”
Section: Eeg Data Processingmentioning
confidence: 99%
“…In correct response trials, the mean EPN amplitude was extracted between 250 and 300 ms after stimulus onset in an occipito‐parietal electrode cluster including electrodes O1, O2, P9, P10, PO7, and PO8 (Kulke, 2019); the mean LPC amplitude in a time window between 400 and 600 ms after stimulus onset in an occipito‐parietal electrode cluster including Pz, POz, PO3, and PO4 (Kulke, 2019); the mean N170 amplitudes were quantified in a time window between 130 and 200 ms after stimulus onset in a posterior electrode cluster (P7, P8, PO7, PO8, PO3, PO4, PO5, PO6) (Hinojosa et al., 2015). The mean no‐go N2 was determined only for correct no‐go trails between 200 and 350 ms in a fronto‐central electrode cluster (Fz, F3, F4, Cz, C3, C4, FCz), based on previous research (Hepsomali et al., 2019; Righi et al., 2009; Sehlmeyer et al., 2010). The frontal response was quantified between 100 and 180 ms in a frontal cluster (F3, FC5, FC3, FC1, C3, F4, FC2, FC4, FC6, C4).…”
Section: Methodsmentioning
confidence: 99%
“…Further frameworks suggest that anxiety negatively impacts individuals' processing efficiency on cognitive Journal of Attention Disorders 25 (13) tasks, such that performance levels similar to non-anxious individuals are only achieved via increased effort or time (Eysenck et al, 2007;Eysenck & Derakshan, 2011). Several studies have found links between reduced efficiency and increased anxiety symptoms in adults, as reflected in slower saccade onsets in an antisaccade task (Hepsomali et al, 2017), as well as greater Contingent Negative Variation (CNV; reflecting greater response preparation) and increased pupillary responses indicating increased effort (Hepsomali et al, 2019).…”
Section: Introductionmentioning
confidence: 99%